The Vulnerability of Syrian Immigrant Pediatric Trauma Patients - Demet Acar; Mustafa Gülpembe; Emin Fatih Vişneci (Eurasian Journal of Emergency Medicine, 2019)

(untitled)
Aim:Worldwide, 22.5 million refugees, half of them children, is a major humanity problem. Refugee children are among the most vulnerable in the world. Recently, we observed an increase in pediatric trauma cases of Syrian immigrant in our hospital. To determine the clinical characteristics of Syrian immigrant children admitted to the emergency department (ED) with trauma with respect to their frequency, socio-demographic characteristics such as living conditions, education of family, not to go to kinder-garden and corresponding high-risk injury.Materials and Methods:This is a retrospective observational study. All records for children aged between 0-17 years were retrospectively evaluated and only patients admitted to the ED with trauma were included in the study. The data of interest investigated from patient records were age, sex, location, and timing of injury occurrence, as well as the family and education data of parents. The mechanisms of injuries were recorded as blunt or penetrating.Results:Totally 200 children with a mean age of 8.29±4.85 years (range: 1-17 years) were included in the study. Falloffs were the most common cause in all age groups. Head injuries were more common compared with the extremities (82 head traumas compared with 60 upper and 32 lower extremity traumas). On the other hand, upper extremity fractures or dislocations were more common compared with the lower extremities (21 vs 3 cases). Interestingly, in this study, among 200 children included, 51 (25.5%) were Syrian immigrants. The mean age of Syrian immigrants was younger than that of Turkish children (p=0.002).Conclusion:In that study, we have determined approximately one-quarter of the children with trauma are Syrian immigrants. Children between the ages of 1-3 years and 6-9 years, and boys were at a higher risk. Syrian immigrants cannot deal with their children enough because of living difficulties for them in Turkey. The living and educational conditions of the Syrian immigrant children who escaped from the war and took refuge should be made better and the sensitivity of the families should be increased. Kinder-garden education highly protects children from house accident so it is necessary especially for Syrian immigrant children.